1996
DOI: 10.3354/meps145269
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of viruses in deep oceanic waters

Abstract: Vertical distributions of bactena and viruses were Investigated in the oceanic stations located in subarctic (Stn A) and subtropical (Stn B) areas of the Paciflc using the direct count technique and transmission electron microscopy. Small DAPI-positive, virus-like particles (VLP) were found to be distributed throughout the water column down to 5000 m a t both of the stations. The abundance of VLP ranged from 38 X 10' ml-' a t 50 m depth to 0.6 X 10' ml-' at 5000 m depth a t Stn A. The ratio of VLP to bacteria-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
86
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 26 publications
22
86
1
2
Order By: Relevance
“…Prokaryotic and viral abundance The average viral abundance in the deep (sub)tropical Atlantic reported in this study was one order of magnitude lower than in the meso-and bathypelagic waters further north in the Atlantic (Parada et al, 2007) but similar to the abundance reported for the deep subtropical Pacific (Hara et al, 1996). Although viral and prokaryotic abundance were related to each other, in agreement with previous studies from the eastern tropical Atlantic (Winter et al, 2008), the virus-to-prokaryote ratio increased from 100 m to 7000 m depth from B10 to B30 (Table 1, Supplementary Figure S2b).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Prokaryotic and viral abundance The average viral abundance in the deep (sub)tropical Atlantic reported in this study was one order of magnitude lower than in the meso-and bathypelagic waters further north in the Atlantic (Parada et al, 2007) but similar to the abundance reported for the deep subtropical Pacific (Hara et al, 1996). Although viral and prokaryotic abundance were related to each other, in agreement with previous studies from the eastern tropical Atlantic (Winter et al, 2008), the virus-to-prokaryote ratio increased from 100 m to 7000 m depth from B10 to B30 (Table 1, Supplementary Figure S2b).…”
Section: Discussionmentioning
confidence: 66%
“…The percentage of the high fluorescence viruses decreased from the epipelagic to the meso-and bathypelagic layers and increased again in the abyssopelagic layers (Supplementary Figure S4). Increasing virus-to-prokaryote ratios with depth have been reported previously (Hara et al, 1996;Fuhrman, 2000;Weinbauer, 2004;Magagnini et al, 2007;Parada et al, 2007). The turnover time of viruses and their decay time, assuming that viral abundance is in steady state, was estimated to range from 11 to 39 days in the bathypelagic North Atlantic (Parada et al, 2007) compared with 1-2 days in near-surface waters (Noble and Fuhrman, 1998;Winter et al, 2004b).…”
Section: Discussionmentioning
confidence: 78%
“…Transport of viruses in deep waters by sinking particles (Hara et al 1996) cannot explain this, since sinking particles are rapidly decomposed within the first 500 m at the study site Dyfamed (Turley and Stutt 2000). Decay of viral infectivity increases with increasing temperature (Cottrell and Suttle 1995), and thus the relatively low temperature of 13ЊC in mesopelagic and deep waters of the Mediterranean Sea and the 4ЊC or less in deep waters of the Indo-Pacific Ocean could have resulted in an increased survival rate of viruses and thus the high VBR values.…”
Section: Discussionmentioning
confidence: 99%
“…Such high retention efficiency of the Anodisc filter is likely due to the surface charge and/or fine sieve-like morphology (Jones et al 1989). In addition, bacterial abundance determined between 0.2 and 0.02 mm pore size Anodisc filters is statistically indistinguishable (Hara et al 1996, Shibata et al 2006. Considering these findings, the retention efficiency of bacterial cells on Anodisc filters can be regarded as being high regardless of pore size; hence, the observed higher bacterial abundance obtained with the SYBR Green I method than with the DAPI method could be due to the difference in filter type as well as pore size.…”
Section: Akiramentioning
confidence: 75%
“…Jones et al (1989) reported that bacterial abundance on the 0.2 mm pore size Anopore filter (renamed Anodisc filter) was 21 to 33% higher than that on the Nuclepore filter of the same pore size when pond water samples were stained with AO. Similarly, from seawater samples, up to 39% of higher bacterial abundance has been determined on the former filter than the latter filter (Hara et al 1996). Such high retention efficiency of the Anodisc filter is likely due to the surface charge and/or fine sieve-like morphology (Jones et al 1989).…”
Section: Akiramentioning
confidence: 99%